The Use of Anaplastic Lymphoma Kinase Inhibitors in Non-Small-Cell Lung Cancer Treatment—Literature Review - Anita Gorzelak-Magiera; Małgorzata Domagała-Haduch; Jacek Kabut; Iwona Gisterek-Grocholska (Biomedicines, 2024)
Lung cancer is the leading cause of cancer-related morbidity and mortality. The median survival time for patients with advanced non-small-cell lung cancer before the era of molecular-based personalized treatment was 7.9 months. The discovery of predictive factors and the introduction of molecular diagnostics into daily practice made a breakthrough, enabling several years of survival in patients with advanced disease. The discovery of rearrangements in the ALK gene and ALK tyrosine kinase inhibitors has resulted in a dramatic improvement in the prognosis of patients with this subtype of cancer. Currently, three generations of ALK inhibitors differing in activity, toxicity and degree of penetration into the central nervous system are available in clinical practice. The current state of knowledge on ALK inhibitors used in clinical practice is summarised in this research paper. Methods of diagnosis of abnormalities in ALK have been shown, and the review of research that contributed to the development of the next generation of ALK inhibitors has been presented.